Development and research of the structure of a digital frequency meter for an instantaneous frequency measurement system - A. N. Lyashuk; P. I. Puzyrev; S. A. Zavyalov (Омский научный вестник)
The article proposes a new method for measuring frequency based on a one-bit ADC. In contrast to the known method of measuring frequency using a delay line, the developed structure of a meter that implements the proposed method makes it possible to get rid of delay lines for measuring frequency in a wide frequency range and to sharply reduce the weight and size parameters of the entire meter with an integrated implementation. Unlike other known digital meters, described in sources, the proposed method makes it possible to increase the accuracy of frequency measurements in a wide frequency range.